Lindley Approximation Technique for the Parameters of Lomax Distribution - Ahmad, Afaq; Fatima, Kawsar; Ahmad, S.P. (International Journal of Statistics in Medical Research, 2017)
The present study is concerned with the estimation of shape and scale parameter of Lomax distribution using Bayesian approximation techniques (Lindley’s Approximation). Different priors viz gamma, exponential and Levy priors are used to obtain the Bayes estimates of parameters of Lomax distributions under Lindley approximation technique. For comparing the efficiency of the obtained results a simulation study is carried out using R-software.